Hubungan Prokrastinasi Akademik Mahasiswa/i terhadap Quarter Life Crisis : Studi Kasus Mahasiswa/i Pendidikan Ekonomi Universitas Panca Sakti Bekasi Tahun Angkatan 2020 s.d 2022 - Ramadhani, Andita; Putrie, Chientya Annisa Rahman (Neolectura, 2023)
This study partially explores the relationship between student procrastination and quarterly crises among undergraduates in the business education program at Pancasakti University Bekasi from 2020 to 2022. while judging empirically. This type of study is a descriptive study that explains or shows the relationship or influence between independent and dependent variables. The research subject consists of students who have completed a course of business education between 2020 and 2022. This study included a sample of 82 respondents, who distributed surveys in batches or via Google From, and each survey via his WhatsApp group. Sampling using non-probative sampling methods using targeted sampling techniques. Hypothesis testing using a simple linear regression test was performed in SPSS 20.0. The results of this study showed that the independent variable of academic procrastination was positively, though not significantly, associated with the dependent variable, quarter-century crisis. The results of this study show that thitung<ttabel value 0,67 < 1,990 then with a decent degree 0,947 > 0,05 Thus, the hypothesis of this study is Ho accepted and Ha rejected. It can be concluded that